Recognition of Microbial Glycolipids by Natural Killer T Cells - Zajonc, Dirk M.; Girardi, Enrico (Frontiers in Immunology, 2015)
T cells can recognize microbial antigens when presented by dedicated antigen-presenting molecules. While peptides are presented by classical members of the Major Histocompatibility (MHC) family (MHC I and II), lipids, glycolipids and lipopeptides can be presented by the non-classical MHC member CD1. The best studied subset of lipid-reactive T cells are Type I Natural killer T (iNKT) cells that recognize a variety of different antigens when presented by the non-classical MHCI homolog CD1d. iNKT cells have been shown to be important for the protection against various microbial pathogens, including B. burgdorferi the causative agents of Lyme disease and S. pneumoniae, which causes pneumococcal meningitis and community-acquired pneumonia. Both pathogens carry microbial glycolipids that can trigger the T cell antigen receptor (TCR), leading to iNKT cell activation. iNKT cells have an evolutionary conserved TCR alpha chain, yet retain the ability to recognize structurally diverse glycolipids. They do so using a conserved recognition mode, in which the TCR enforces a conserved binding orientation on CD1d. TCR binding is accompanied by structural changes within the TCR binding site of CD1d, as well as the glycolipid antigen itself. In addition to direct recognition of microbial antigens, iNKT cells can also be activated by a combination of cytokines (IL-12/IL-18) and TCR stimulation. Many microbes carry TLR antigens and microbial infections can lead to TLR activation. The subsequent cytokine response in turn lower the threshold of TCR mediated iNKT cell activation, especially when weak microbial or even self-antigens are presented during the cause of the infection. In summary, iNKT cells can be directly activated through TCR triggering of strong antigens, while cytokines produced by the innate immune response may be necessary for TCR triggering and iNKT cell activation in the presence of weak antigens. Here we will review the molecular basis of iNKT cell recognition of glyc